2017
DOI: 10.1016/j.pedn.2016.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of the Influence of Factors Identified in the Literature on School-aged Children's Emotional Responses to Asthma

Abstract: Approximately 6.3 million US children suffer from asthma. The purpose of this study was to explore factors on school-aged children’s emotional responses to asthma, N=85, ages 6–12. Correlations included Asthma related child emotional functioning QOL and (a) asthma severity, r = −.30, p <.01, (b) child internalizing behaviors, r = −.26, p < .05, (c) child externalizing behaviors r = −.43, p <.001; Caregiver emotional functioning QOL and (a) asthma severity, r = −.39, p <.001, (b) child internalizing behaviors, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 52 publications
0
5
1
Order By: Relevance
“…Additionally, among Thabrew’s findings [ 51 ], it was highlighted that cyber-interventions are not effective in improving the quality of life of asthmatic children and that new technological tools need to be developed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, among Thabrew’s findings [ 51 ], it was highlighted that cyber-interventions are not effective in improving the quality of life of asthmatic children and that new technological tools need to be developed.…”
Section: Resultsmentioning
confidence: 99%
“…For this reason, the quality of life of these children depends on the degree of control of the disease on their part; if the disease is under their control, the quality of life will be better. On the other hand, if the parents turn the child into what is known as a “fragile child” by preventing them from acquiring the competencies to cope with the disease on their own during the course of their life, their quality of life will be reduced [ 51 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…The emotional sub-scale explored how often children felt upset, anxious, worried, or distressed because of their asthma and how often they were frightened by an asthma attack. 40 …”
Section: Discussionmentioning
confidence: 99%
“…In the United States, it was reported that there was slightly poorer emotional processing in Hispanic children in comparison with the non-Hispanic White and Black children. The emotional sub-scale explored how often children felt upset, anxious, worried, or distressed because of their asthma and how often they were frightened by an asthma attack 40 …”
Section: Discussionmentioning
confidence: 99%
“…Another study conducted in the United States found that the following clinical and familial factors were strongly related with the HRQL result as measured by the PAQLQ: The length of nocturnal symptoms, the number of visits to the primary care physician, the quality of control, and family losses and transitions [36] .…”
Section: Possible Predictors Of Pediatric Asthma Quality Of Lifementioning
confidence: 99%